Concomitant Administration of a Histamine2 Receptor Antagonist and Proton Pump Inhibitor Enhances Gastric Acid Suppression. Issue 12 (1st December 2015) - Abdul‐Hussein, Mustafa; Freeman, Janice; Castell, Donald
Abstract : Study Objective: Because it has been hypothesized that histamine2 receptor antagonists (H2 RAs) might interfere with the action of proton pump inhibitors (PPIs) when the drugs are given concomitantly, we sought to compare the pharmacodynamic effects of simultaneous administration of a PPI and an H2 RA with the effects of each drug administered alone. Design: Prospective, randomized, double‐blind, three‐way crossover study. Setting: Esophageal motility laboratory at a large teaching hospital. Subjects: Twenty‐one healthy volunteers. Intervention: Subjects were randomized to one of three treatment arms: an H2 RA (ranitidine 300 mg) plus placebo, a PPI (omeprazole 40 mg) plus placebo, or ranitidine 300 mg plus omeprazole 40 mg, all given once/day at 8a.m ., 30 minutes before a standard breakfast, for 1 week. The subjects then received the other two treatments, with each treatment period separated by a 1‐week washout period. Measurements and Main Results: The primary outcome was length of time that the gastric pH remained higher than 4. Secondary outcomes were median gastric pH higher than 4 and percentage of time that the gastric pH remained higher than 4. On day 7, ambulatory intragastric pH was recorded over an 8‐hour period in each treatment arm. The combination of ranitidine and omeprazole resulted in a significantly longer time that the gastric pH remained higher than 4 (median 410.5 min [interquartile range (IQR) 298.5–454.25 min]) versus either omeprazole alone (median 356.7 min [IQR 254.9–419.2 min], p=0.023) or ranitidine alone (134.1 min [IQR 99.9–302.5 min], p<0.0001). Median gastric pH was also significantly higher when omeprazole and ranitidine were given in combination (pH 5.92 [IQR 4.75–6.46]) than either omeprazole alone (pH 4.88 [IQR 4.27–6.11], p=0.001) or ranitidine alone (pH 2.31 [IQR 2.04–5.27], p=0.0003). Likewise, the percentage of time that the gastric pH remained higher than 4 was significantly higher when omeprazole and ranitidine were given in combination (median 85.52%) than either omeprazole alone (74.31%, p=0.027) or ranitidine alone (27.94%, p=0.0002). Conclusion: When a PPI and H2 RA were administered concomitantly 30 minutes before breakfast, the H2 RA did not decrease the acid suppressive ability of the PPI; rather, it improved gastric acid control. Thus these results failed to support the initial hypothesis of this study. Further prospective studies are needed to test these findings in patients with gastroesophageal reflux disease as well as those with erosive esophagitis.